Pengaruh Religiusitas Terhadap Kedisiplinan Siswa di SMA Muhammadiyah Kasihan Bantul Yogyakarta - Maria Yhuva (FAI, 2017)
Pengaruh Religiusitas Terhadap Kedisiplinan Siswa di SMA Muhammadiyah Kasihan Bantul Yogyakarta